1993
DOI: 10.1522/1486981
|View full text |Cite
|
Sign up to set email alerts
|

Techniques isotopiques (15N 18O) appliquees a l etude des nappes des alterites et du socle fracture de l ouest africain

Abstract: V modifiée par des phénomènes comme la dénitrification ou l'adsorbtion des nitrates sur les oxi-hydroxides.Les résultats de cette étude suggèrent qu'indépendamment de la taille des bassins versants, la recharge des aquifères de fracture du socle semble contrôlée par le réseau fracturé et les cours d'eau qui empruntent des accidents majeurs. Par ailleurs, la contamination des nappes par les nitrates semble être le résultat d'une urbanisation sauvage (latrines artisanales) et de la deforestation. Alors que les p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…Rainfall data were obtained from the International Atomic Energy Agency (IAEA) network (GNIP, 2011), from Niamey/ORSTOM stations (1992 to 1999) and IRI/Abdou Moumouni University of Niamey in Niger, located at an almost identical (190 m vs 225 m asl) altitude (Ousmane, 1988;Girard, 1993, Taupin et al, 2002, Guéro, 2003, Tremoy et al, 2012.…”
Section: Chemical and Isotope Analysesmentioning
confidence: 99%
“…Rainfall data were obtained from the International Atomic Energy Agency (IAEA) network (GNIP, 2011), from Niamey/ORSTOM stations (1992 to 1999) and IRI/Abdou Moumouni University of Niamey in Niger, located at an almost identical (190 m vs 225 m asl) altitude (Ousmane, 1988;Girard, 1993, Taupin et al, 2002, Guéro, 2003, Tremoy et al, 2012.…”
Section: Chemical and Isotope Analysesmentioning
confidence: 99%
“…During the dry season, particularly from March to May, the Harmattan brings temperatures of up to 50°C. Hydric deficits are thus major and surface water resources are almost non-existent, leaving only alluvial underground water for use by inhabitants (Girard, 1993). This has a negative impact on agriculture, which is an important economic activity but only weakly represented in terms of land use distribution.…”
Section: General Contextmentioning
confidence: 99%
“…The groundwater depth of the Niger Liptako aquifer is between 0 (Niger River) and 75 m and feeds mainly Niamey City. Other studies (Girard, 1993) have shown that some boreholes provide water unfit for human consumption (nitrogen pollution), while others are quickly drained. Hydro-geological characteristics such as aquifer recharge and sustainability are thus very difficult to understand in fractured basement.…”
Section: -Faults Of the North Continental Terminal Basin (N-s And N-smentioning
confidence: 99%
See 1 more Smart Citation
“…Au Niger, le rôle de la fracturation dans l'hydrodynamique souterraine est démontré par les travaux antérieurs (Ousmane, 1988 ;Girard, 1993 ; Corgne et al, 2010; Abdou Babaye, 2012).…”
Section: Introductionunclassified